Which is more predictive ovarian sensitivity marker if there is discordance between serum anti-Müllerian hormone levels and antral follicle count? A retrospective analysis. (4th July 2022) - Aslan, Kiper; Kasapoglu, Isil; Cakir, Cihan; Koc, Meltem; Celenk, Murat Deniz; Ata, Baris; Avci, Berrin; Uncu, Gurkan
Abstract: This retrospective study aims to determine the more predictive ovarian reserve marker when there is discordance between anti-Müllerian hormone (AMH) and antral follicle count (AFC) in patients with diminished ovarian reserve (DOR). Patients who underwent ICSI because of DOR were divided into three groups. Group 1: patients with low AMH (<1.1 ng/ml) and AFC ( n < 7), group 2: patients with low AMH (<1.1 ng/ml) and normal AFC ( n ≥ 7) and group 3: patients with normal AMH (≥1.1 ng/dl) and low AFC ( n < 7). Demographic values, follicle output rate (FORT) score and follicle to oocyte index (FOI) score of the groups were compared. Totally, 662 cycles were enrolled in the study. There were 418 cycles in group 1, 167 cycles in group 2 and 77 cycles in group 3. As the primary result, FORT and FOI scores were higher in group 3 than the other two groups. Median FORT Score with quartiles: group 1: 100 (66–150), group 2: 71 (57–100), group 3: 136 (96–200), p <.01 – median FOI score with quartiles: group 1: 83 (50–140), group 2: 71 (40–100), group 3: 116 (66–216), p <.01. In conclusion, serum AMH level has more predictive value for stimulation success if there is discordance with AFC. Impact Statement: What is already known on this subject? Female age, serum Anti-Müllerian Hormone (AMH) levels, and antral follicle count (AFC) are commonly used to assess ovarian reserve and predict response to ovarian stimulation. AMH and AFC are both positively correlated with ovarian reserve. What do the results of this study add? If there is discordance between AFC and AMH in patients with diminished ovarian reserve (DOR), the ovarian response is better in patients with high AMH and low AFC than the patients with low AMH and high AFC. What are the implications of these findings for clinical practice and/or further research? It is important to assess both AFC and AMH before controlled ovarian hyperstimulation, to predict ovarian response in DOR patients, rather than assessing AFC or AMH alone.